Analisis Struktur Modal, Kebijakan Dividen, dan Volatilitas Pendapatan terhadap Kinerja Emiten Terbaik - Nidar, Sulaeman Rahman (Jurnal Trikonomika, 2010)
Financial condition of firms is one of the main concerns of investor in a capital market. At present, Investor does not need to calculate and analyze listed company performance himself. One of the magazines which informs listed company performance is Majalah Investor. One of the information is the 100 best listed companies annual of JSX. Rank of the best listed company changed annually, and it is needed to be analyzed for investigating which factors influence listed companies to become the best listed companies rank. The research employs 37 listed companies from the 100 best listed companies Majalah Investorâs version. This research attempts to investigate interdependence mechanism among capital structure, dividend policy, earnings volatility and performance of the firm. The research findings that performance of the firm partially and simultaneously is influenced by capital structure, dividend policy, and earnings volatility. And the 100 best listed companies reported by Majalah Investor for 2004â2005, indicate that abnormal return for 10 days before and after announcement of the report have no significant influence on performance of the firm. Market does not give any significant reaction to the announcement.